2013
DOI: 10.1007/s00330-013-2803-4
|View full text |Cite
|
Sign up to set email alerts
|

“Dynamic spot sign” on CT perfusion source images predicts haematoma expansion in acute intracerebral haemorrhage

Abstract: • It is important to identify potential progression of spontaneous intracerebral haemorrhage. • Dynamic enhancement within CT perfusion source images is associated with haemorrhage expansion. • The CTP dynamic spot sign may be present throughout arterial to venous phase imaging. • The CTP dynamic spot sign carries a higher predive value for haematoma expansion than CTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…Hallevi et al 18 demonstrated that contrast extravasation on PCCT was a more sensitive predictor of hematoma expansion than the spot sign, and Ederies et al 13 demonstrated that PCCT leakage in addition to the spot sign improved sensitivity for hematoma expansion. More recent studies using dynamic CTA 17 and CTP 20,21 showed improved detection of the spot sign and increased accuracy for predicting outcome and hematoma expansion. Although it is clear that the spot sign is a dynamic finding, there is no accepted consensus regarding the timing of image acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Hallevi et al 18 demonstrated that contrast extravasation on PCCT was a more sensitive predictor of hematoma expansion than the spot sign, and Ederies et al 13 demonstrated that PCCT leakage in addition to the spot sign improved sensitivity for hematoma expansion. More recent studies using dynamic CTA 17 and CTP 20,21 showed improved detection of the spot sign and increased accuracy for predicting outcome and hematoma expansion. Although it is clear that the spot sign is a dynamic finding, there is no accepted consensus regarding the timing of image acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies propose a ‘dynamic spot sign' using CT perfusion, a quantitative technique which allows a real-time contrast extravasation measurement. The dynamic spot sign seems to be a better prognostic marker than the CTA spot sign with higher sensitivity and predictive value [42,43,44], however, it needs to be standardised and validated.…”
Section: Discussionmentioning
confidence: 99%
“…The spot sign is associated with hematoma expansion and increased mortality. 35,36 In a prospective evaluation, Sun et al 37 found the spot sign to be present throughout the arterial-to-venous phases on 4D-CTA studies of 112 patients and it was an independent predictor of hematoma progression. In comparison with conventional CTA, the spot sign on 4D-CTA had a higher predictive value for hematoma expansion; therefore, 4D-CTA seems to be more accurate for estimating prognosis.…”
Section: Classification Of Arteriovenous Malformations and Arteriovenmentioning
confidence: 99%